Public libraries and the information society, de J. Thourhauge e G. Larsen - Suaiden, Emir José (Revista de Biblioteconomia de Brasília, 1997)
THOURHAUGE, J.; LARSEN, G. Public libraries and the information society. Luxembourg : European Comission, 1997. 352 p.